Renormalization flow of axion electrodynamics - Eichhorn, Astrid; Gies, Holger; Roscher, Dietrich (Arxiv, 2012)
We study the renormalization flow of axion electrodynamics, concentrating on the non-perturbative running of the axion-photon coupling and the mass of the axion (like) particle. Due to a non-renormalization property of the axion-photon vertex, the renormalization flow is controlled by photon and axion anomalous dimensions. As a consequence, momentum-independent axion self-interactions are not induced by photon fluctuations. The non-perturbative flow towards the ultraviolet exhibits a Landau-pole-type behavior, implying that the system has a scale of maximum UV extension and that the renormalized axion-photon coupling in the deep infrared is bounded from above. Even though gauge invariance guarantees that photon fluctuations do not decouple in the infrared, the renormalized couplings remain finite even in the deep infrared and even for massless axions. Within our truncation, we also observe the existence of an exceptional RG trajectory, which is extendable to arbitrarily high scales, without being governed by a UV fixed point.
Gesehen am 11.01.2018